Factors influencing the well-being of primary school teachers in Indonesia: a pilot study - Saleh, Airin Yustikarini; Kurniawati, Farida; Salim, Rose Mini Agoes; Poerwandari, Elizabeth Kristi (Psychological Research on Urban Society, 2024)
Understanding and improving teacher well-being are essential prerequisites for effective teaching. However, studies on teacher well-being in Indonesia are few. This mixed-method study was conducted to identify the factors that influence the well-being of teachers in primary schools in Indonesia. Data were collected through self-rating and open-ended questions from 209 primary school teachers followed by semi-structured interviews with eight teachers. The results of the self- rating survey illustrated that the teachers were very satisfied with their lives as a teacher. Well-being was considered important in their work, because it can exert a positive impact on students. The results of the thematic analysis demonstrated that relational and professional dimensions are the most frequently cited themes in the responses as factors that support and inhibit well-being. The lack of learning facilities and infrastructure in schools are cited as the most inhibiting factors. The study discussed potential explanations for the findings in relation to teacher well-being.